2009
DOI: 10.2119/molmed.2009.00005
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatic Response to Thermal Injury: Is the Liver Important for Postburn Outcomes?

Abstract: Thermal injury produces a profound hypermetabolic and hypercatabolic stress response characterized by increased endogenous glucose production via gluconeogenesis and glycogenolysis, lipolysis, and proteolysis. The liver is the central body organ involved in these metabolic responses. It is suggested that the liver, with its metabolic, inflammatory, immune, and acute phase functions, plays a pivotal role in patient survival and recovery by modulating multiple pathways following thermal injury. Studies have eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 134 publications
3
102
0
2
Order By: Relevance
“…1). These findings reconfirmed both liver and spleen are the primary target organs in host immune deficit after burn injury [20,29] .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…1). These findings reconfirmed both liver and spleen are the primary target organs in host immune deficit after burn injury [20,29] .…”
Section: Discussionmentioning
confidence: 55%
“…The prominent character of post-burn T cell suppression is the depletion of T cells. Moreover, cumulative findings suggested that the liver with its immune, inflammatory and acute phase functions plays a pivotal role in survival and recovery of patients following burn injury [29,30] . Therefore, we confirmed the depletion of HMNCs as well as SMNCs after burn injury (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…58,59 Investigating the pro-regenerative aspects of the cell types discussed above may assist in enhancing the recovery and survival of patients' post-hepatectomy and possibly after trauma, such as a severe burn. 60 Thus, despite the divergence, the compensatory response after liver resection is clinically essential and provides a great model to learn about growth and regeneration. A better understanding of how cells in the liver interact and respond to their microenvironment will give us the ability to pinpoint aberrant healing and develop novel therapies to treat liver disease.…”
Section: Clinical Insights Into Liver Regenerationmentioning
confidence: 99%
“…Blood flow is increased to both the liver and kidneys because of enhanced cardiac output. In the liver, the synthesis of constitutive proteins (eg, albumin and transferrin) is geared towards acute phase protein synthesis (eg, α 1 -acid glycoprotein and fibrinogen) to maintain immune function, wound healing, and coagulation processes [12]. These changes lead to alterations in the protein binding of drugs, especially highly protein-bound, acidic drugs.…”
Section: Pharmacokinetic and Pharmacodynamic Alterations In Burn Patimentioning
confidence: 99%